Una nueva especie de Elaphoglossum sección Elaphoglossum (Lomariopsidaceae) en Costa Rica - Rojas Alvarado, Alexander Francisco (Lankesteriana: International Journal on Orchidology, 2015)
The new species Elaphoglossum lenticulatum, sect. Elaphoglossum subsect. Pachyglossa, is described here. This species is segregated from E. proximum (J. Bommer) H. Christ because of entire (vs. ciliate), persistent (vs. deciduous) and bigger rhizome scales, lanceolate (vs. lanceolate-oblong) blade, and less dense and bigger blade scales.